Generativity and Psychological Well-Being in Primary and Secondary Teachers: A Systematic Review - Villalta-Paucar, M (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Background: Teaching represents a highly demanding profession in emotional, social and cognitive terms, demanding a genuine interest in contributing to the development of future generations. Precisely for this reason, generativity, understood as the genuine interest in contributing to the care and development of future generations, and psychological well-being, defined as the integration of autonomy, life purpose and positive relationships, are key variables to understand the integral development of teachers. However, the relationship between both constructions in primary and secondary school teachers emerges as an emerging theme that is scarcely researched in the local context. Method: Following the PRISMA-ScR guidelines, this exploratory review used WOS, Scopus, ERIC, Scielo, and PsycNet databases to analyze the available literature on the interplay between generativity and psychological well-being in primary or secondary school teachers exploring its manifestations and the contextual factors (rural/urban) that shape this dynamic. We included 11 studies published up to 2025. Results: The studies analyzed show that generativity strengthens the sense of life and teacher commitment, while psychological well-being would modulate resilience to stress and pedagogical effectiveness. However, the literature presents conceptual and methodological heterogeneity. The theoretical gaps and methodological limitations of the findings are discussed, highlighting the importance of moving towards integrative frameworks that strengthen the mental health of teachers in the digital society. Conclusion: Generativity and psychological well-being are deeply interconnected in teaching practice yet remain under-theorized in educational research. This review highlights the need for integrative frameworks that support teachers’ mental health and professional identity, especially in diverse and evolving educational contexts. © 2025 by the authors.